Standard methods of chemical analysis : a manual of analytical methods and general reference for the analytical chemist and for the advanced student : special subjects - Scott, Wilfred W. (Van Nostrand)
Contenido: Muestreo, tratamiento preliminar y análisis aplicados. Técnicas especiales, aplicables a diversas sustancias.